Clinical management of type C hepatic encephalopathy. Issue 5 (June 2020) - Ridola, Lorenzo; Riggio, Oliviero; Gioia, Stefania; Faccioli, Jessica; Nardelli, Silvia
Type-C hepatic encephalopathy is a complex neurological syndrome, characteristic of patients with liver disease, causing a wide and complex spectrum of nonspecific neurological and psychiatric manifestations, ranging from a subclinical entity, minimal hepatic encephalopathy, to a deep form in which a complete alteration of consciousness can be observed: overt hepatic encephalopathy. Overt hepatic encephalopathy occurs in 30–40% of patients. According to the time course, hepatic encephalopathy is subdivided into episodic, recurrent and persistent. Diagnostic strategies range from simple clinical scales to more complex psychometric and neurophysiological tools. Therapeutic options may vary between episodic hepatic encephalopathy, in which it is important to define and treat the precipitating factor and hepatic encephalopathy and secondary prophylaxis, where the standard of care is non-absorbable disaccharides and rifaximin. Grey areas and future needs remain the therapeutic approach to minimal hepatic encephalopathy and issues in the design of therapeutic studies for hepatic encephalopathy.